Some Gublite Artifact Possibly Made at Ebla - Pinnock, Frances (Syria, 2012)
This contribution aims at analyzing some objects from a votive deposit in the area of the Obelisks Temple of Byblos, jar 16694. These objects, in the interpretation proposed here, might have been made in palace workshops of Ebla, for the presence of some strong elements of comparison with productions peculiar to the great centre of north inner Syria. Moreover, a hypothesis is proposed about the circumstances which led to the creation and burial of the deposit of jar 16694, and about the titular deity of the Obelisks Temple. According to this hypothesis, as first maintained by M. Dunand, the god should be Rašap, god of war, plague, and of the Netherworld.